1976
DOI: 10.1017/s0003356100035583
|View full text |Cite
|
Sign up to set email alerts
|

Intake by and performance of early-weaned calves offered unwilted or wilted silage supplemented with a cereal and protein concentrate or dried grass

Abstract: Intake by and performance of early-weaned calves offered unwilted or wilted silage supplemented with a cereal and protein concentrate or dried grass R. Marsh SUMMARY Forty-two British Friesian castrated male calves of 1 to 3 weeks of age were offered ad libitum unwilted or wilted silage made from the same sward for 21 consecutive weeks. Both silages were supplemented with a cereal and protein concentrate at two restricted levels of intake or with dried grass cobs offered ad libitum. There was little difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

1979
1979
1994
1994

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…We found, in agreement with the results of other authors (Marsh, 1976;Zduhczyk and Lewicki, 1989), that limiting the ration of concentrate stimulates the intake of silage (the ratio of dry matter intake from concentrate to that from roughage in groups H and S was similar and equalled 1.3 and 1.4, respectively), and the silage, in spite of its low DM content (18.9%) was comparable to hay as a source of nutrients for the calves.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…We found, in agreement with the results of other authors (Marsh, 1976;Zduhczyk and Lewicki, 1989), that limiting the ration of concentrate stimulates the intake of silage (the ratio of dry matter intake from concentrate to that from roughage in groups H and S was similar and equalled 1.3 and 1.4, respectively), and the silage, in spite of its low DM content (18.9%) was comparable to hay as a source of nutrients for the calves.…”
Section: Resultssupporting
confidence: 94%
“…However, it has been demonstrated that good quality grass silage can be included in hay-free diets for young calves even of the age of two weeks (Bartholomew etal., 1981;Marsh, 1975Marsh, ,1976. According to Marsh (1975) when fattened calves were provided with limited amounts of concentrates and grass silage fed to appetite, satisfactory weight gains were achieved and 35% less concentrate was consumed in comparison with traditional feeding regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Krosowski and KTosowska (1984) and KTosowski et al (1988) reported that the faster the animals' growth as affected by feeding, the larger the fibre diameter and higher the percentage of FTG fibers. In growing calves reared on hayfree low-concentrate diets based on grass silage, satisfactory gains have been reported (Marsh, 1975(Marsh, , 1976Bartholomew et al, 1981;Bidwell-Porgbska et al, 1987;Piotrowski et al, 1988) (Ziegan, 1979 (Brooke, 1970) In the younger calves the intake of crude protein (CP) and gross energy (GE) was also slightly higher in the SD fed group. In the older animals the daily intake of GE was considerably higher, while the intake of CP was lower in the SD than in the HD fed group (table I).…”
mentioning
confidence: 97%